IMPLEMENTING JAS (NATURAL SURROUNDING EXPLORATION) BASED PLANT DETERMINATION PRATICUM MODEL AT KELIMUTU NATIONAL PARK - Jumilah Gago; Veronika P. Sinta Mbia Wae Veronika P. Sinta Mbia Wae (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to implement models and learning tools based on integrated JAS (Natural Surrounding Exploration) approach in the plant taxonomy course particularly plant determination material. This research was conducted by utilizing descriptive method with a qualitative approach. The research was conducted from September to November 2019 in the odd semester at the academic year 2019/2020. The samples were chosen by purposive sampling technique. The samples were 43 students of biology education study program at Universitas Flores who took plant taxonomy course. The research was conducted at Kelimutu National Park. Based on the results, the use of a taxonomic learning model based on natural surrounding exploration was considered quite interesting and encouraged meaningful teaching and learning activities. In addition, based on the results of interviews with biology students, this method provided advantages including (1) being able to increase students' understanding of plant identification, (2) being an attractive medium to trigger learning motivation because it was related to the real context around it, and (3) instilling a caring attitude and love for the natural wealth around and the culture around it.